Radicalism Prevention through Propaganda Awareness on Social Media - Yani Tri Wijayanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
Dissemination of information through social media is prone to high school students because of its high social media usage activities. Students need to have propaganda awareness (awareness of the existence of propaganda practices), which is mainly disseminated through news or other media content. By having propaganda awareness, students can analyze information or news, so they can sift essential information, including information that they wish to redistribute. This research used a mixed method. The data was collected with a focus group discussion and propaganda test to students of State Madrasah Aliyah (MAN) in the Yogyakarta Special Province. The result of the propaganda test before the simulation showed the strong influence of the media on student attitudes. After simulation and retesting, the effect decreased significantly. Propaganda awareness can be a provision for students to be more alert in filtering information from social media that contain radicalism.